ANALYZING EYE MOVEMENTS AND ITS EOG SIGNALS USING WALSH TRANSFORM (American Journal of Interdisciplinary Research and Development, 2023)
The Walsh Transform was used in this research to extract and study the EOG signal of eye movements and its features. Four types Of EOG signals were measured, vertical eye movements (UP, down) Horizontal eye movements (Left and right). The measured EOG signals were filtrides then transformed using WHT and then reconstructed. A measurement system built using Arduino-like OLIMEX 328 microcontroller with two EMG shields.